Examining the Impact of Macro-Economic Conditions on Income Inequality - Markus Jäntti; Stephen P. Jenkins (Institute for the Study of Labor (IZA), 2001)
This paper proposes a new approach for analyzing the relationship between macroeconomic factors and the income distribution. The conventional method of analysis is regression of summary inequality indices on variables such as the unemployment and inflation rates. Building on the lessons from recent advances in time-series econometrics, we suggest instead that one should first fit a parametric functional form to the income distribution for each year, and then model the time series of model parameters in terms of the macroeconomic factors. Inferences about the relationship between the income distribution and macroeconomic factors can be derived from the model estimates. We apply these methods to data from the United Kingdom for 1961-91, and contrast the results with those found using earlier methods.
Keywords: E6; C51; D31; 330; Income inequality; macro-economic conditions; unemployment; inflation; Singh-Maddala distribution; Einkommensverteilung; Makroökonomischer Einfluß; Arbeitslosigkeit; Inflation; Zeitreihenanalyse; Schätzung; Theorie; Großbritannien; Singh-Maddala distribution